ChemInform Abstract: Copper‐Mediated Perfluoroalkylation of Heteroaryl Bromides with (phen)CuRF. Issue 36 (9th September 2014) - Mormino, Michael G.; Fier, Patrick S.; Hartwig, John F.
Abstract The reaction with the phenanthroline‐ligated perfluoroalkyl copper reagents is applied to a wide range of heteroaromatic bromides.